Overview of Three Proliferation Pathways (Wnt, Notch, and Hippo) in Intestine and Immune System and Their Role in Inflammatory Bowel Diseases (IBDs) - Khoramjoo, Seyed Mobin; Kazemifard, Nesa; Baradaran Ghavami, Shaghayegh; Farmani, Maryam; Shahrokh, Shabnam; Asadzadeh Aghdaei, Hamid; Sherkat, Ghazal; Zali, Mohammad Reza (Frontiers in Medicine, 2022)
Inflammatory bowel disease (IBD) is a disorder, which involves the gastrointestinal (GI) tract consisting Crohn's disease (CD) and ulcerative colitis (UC). The etiology of this disease is not yet clear and, hence, there are numerous medications and treatments for patients with IBD, although a definite and permanent treatment is still missing. Therefore, finding novel therapeutic approaches are vital for curing patients with IBD. In the GI tract, there are various lineages of cells with different roles that their existence is necessary for the barrier function of intestinal epithelial cells (IECs). Therefore, signaling pathways, which manage the hemostasis of cell lineages in intestine, such as Wnt, Notch, and Hippo, could have crucial roles in regulation of barrier function in the intestine. Additionally, these signaling pathways function as a governor of cell growth, tissue homeostasis, and organ size. In patients with IBD, recent studies have revealed that these signaling pathways are dysregulated that it could result in depletion or excess of a cell lineage in the intestine. Moreover, dysregulation of these signaling pathways in different cell lineages of the immune system could lead to dysregulation of the immune system's responses in IBD. In this article, we summarized the components and signaling of Wnt, Notch, and Hippo pathways and their role in the intestine and immune system. Furthermore, we reviewed latest scientific literature on the crosstalk among these three signaling pathways in IBD. An overview of these three signaling pathways and their interactions in IBD could provide a novel insight for prospective study directions into finding efficient medications or treatments.